2010
DOI: 10.6026/97320630004417
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR study on some series of anti-hepatitis B virus (HBV) agents

Abstract: A quantitative structure­activity relationship (QSAR) study has been made on some series of anti­hepatitis B virus (HBV) agents, namely, a series of novel bis(L­amino acid) ester prodrugs of 9­[2­­(phosphonomethoxy)ethyl]adenine, a similar series of compounds comprising of 2­ amino­6­arylthio­9­[2­(phosphonoethoxy)ethyl] purine bis(2,2,2­ trifluoroethyl) esters, and a series of 1­isopropylsulfonyl­2­amine benzimidazoles. In each case significant correlations are found between the anti­HBV potencies and some ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It suggested that for enhancing activity of drug, particular descriptors have to be maximized. Although many QSAR studies have been carried out previously on several anti HBV compounds but the current study, on the antiviral activity of these compounds against Hepatitis B, is unique in nature [16]. This kind of computational approach will help in adding up a new antiviral agent in the list, extracted from the existing drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggested that for enhancing activity of drug, particular descriptors have to be maximized. Although many QSAR studies have been carried out previously on several anti HBV compounds but the current study, on the antiviral activity of these compounds against Hepatitis B, is unique in nature [16]. This kind of computational approach will help in adding up a new antiviral agent in the list, extracted from the existing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Along with providing guidelines for the drug design, QSAR also sheds light on the mechanisms of drug-receptor interactions, which further assist to the rationalization of drug development. We, therefore, present here a QSAR study selected anti HBV compounds [16]. Different software such as ChemDraw [17], HyperChem [18], AutoDock [13] and VMD [14] were selected and used to get the results.…”
Section: Figure 1 Drug Designing Schemementioning
confidence: 99%
“…org).9 A set of standard ligands ( Table 1) that inhibit the replication of the viral core protein were taken from the literature. 10 The ligands docked onto the active site of HBV core protein using Autodock 4.2,11 Autodock vina12 and Plats program. 13 The best ligand result that be continued to molecular dynamic simulation by Amber 14.14…”
Section: Methodsmentioning
confidence: 99%
“…10 The docking set consist derivates of bis (L-amino acid) ester prodrugs of 9-[2-(phosphonomethoxy)ethyl] adenine (PMEA), Lamivudine and Adefovir dipivoxil with IC 50 value. To validate the simulation model, that compounds ware used as a test set (see Table 1).…”
Section: Selection Of Standard Compoundsmentioning
confidence: 99%
“…For example, ChEMBL, PubChem—a database of molecules and their activities, ZINC—database of commercial compounds for virtual screening, and DrugBank—a knowledgebase for drugs and drug targets . In addition, there are a few QSAR studies targeting specific viral proteins . However, till date there is no web server/software, which can regressively predict the percentage inhibition value of a compound against different human viruses under a single platform.…”
mentioning
confidence: 99%